Jerry ou comment faire parler autrement les murs - Sterlin Ulysse (Les Cahiers de Framespa)
In 2007, the inhabitants of Port-au-Prince discovered on various walls inscriptions and drawings, signed by «Jerry», which sometimes delivered social or moral messages, and sometimes supported the opposite view by distorting them. How can we interpret the real motivation of the tagger? However, after the earthquake of January 12, 2010, his identity was revealed, thanks to several NGOs which hired the tagger to pass on their messages of mobilization in the camps. People then realized that Jerry's work questions traditional politics, just like the young people living in popular districts. Through graffiti, he denounces and claims what the rappers denounce and claim through words. Jerry has never wanted to stay in the shadow. Like young people from popular districts, he tries to remain in the spotlights. How does sociopolitical reality enable us to better understand Jerry's work as a way for him to reach completion and as an attempt to display the real problems of the country?